COVID-19 pandemic: an Italian single institution’s experience and lessons learned by public health residents’ workforce - Tocco-Tussardi, I.; De Mattia, G.; Gasabelli, V.; Mazzer, M.; Vanin, S.; Ramaroli, D. A.; Schiesaro, G.; Salandini, G.; Varalta, M. S.; Benoni, R.; Zanetel, E.; Fagherazzi, J.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Coronavirus Disease 2019 pandemic has posed incredible challenges to healthcare workers worldwide. The residents have been affected by an almost complete upheaval of the previous setting of activities, with a near total focus on service during the peak of the emergency. In our Institution, residents in public health were extensively involved in leading activities in the management of Coronavirus Disease 2019 pandemic.Methods. We hereby provide a systematic description of the response actions in which the public health residents’ workforce was pivotal, in a large tertiary hospital.Results. The key role played by residents in the response to Coronavirus Disease 2019 pandemic is highlighted by the diversity of contributions provided, from cooperation in the rearrangement of hospital paths for continuity of care, to establishing and running new services to support healthcare professionals. Overall, they constituted a workforce that turned essential in governing efficiently such a complex scenario. Conclusions. Despite the difficulties posed by the contingency and the sacrifice of many training activities, Coronavirus Disease 2019 pandemic turned out to be a unique opportunity of learning and measuring one’s capabilities and limits in a context of absolute novelty and uncertainty.